From China's Reform to the World's Reform. Issue 2 (2nd April 2020) - Hrubec, Marek
ABSTRACT: The article explains that the Chinese Belt and Road Initiative, as a distinct Globalisation 2.0, is not only an innovative activity born after the 2008 global financial and economic crisis, but that there are also deeper important causes behind mainly in the more than 40 years of China's reform and opening up since 1978. It illuminates why the reform and opening up can be considered a "revolutionary transformation, " and how it has passed the stages of its development, with its guiding principles, changes in the spheres of planning, the market, and kinds of ownership. The article explains how it leads to the Belt and Road Initiative as a reform of global interactions.